Clinicopathological features of Differentiated Thyroid Cancer presenting in the UK versus internationally: An observational cohort study. (11th January 2021) - Sawant, R.; Hey, S.Y.; Hulse, K.; Hay, A.; Gibb, F.W.; Adamson, R.; Nixon, I.J.
Abstract: Introduction: Very little data are available regarding differentiated thyroid cancer (DTC) managed in the UK, and no UK patients are included in the evidence base upon which international guidelines are based. Therefore, the aim of this study was to compare the clinicopathological features of patients with DTC presenting in a UK population with international patient cohorts. Patients and methods: Data were collected from a prospectively held multi‐disciplinary team records from January 2009 to December 2016. The local cohort was compared with cohorts from across the world based on clinicopathological features. Ethical approval was obtained by Lothian Caldicott Guardian (Ref 16 133). Results: 444 cases were diagnosed locally with a median age of 48 years (range 16‐86 years). 78% of patients were female. 25% of our patients had follicular carcinoma with an overall N1 rate of 20%. Distant disease was recorded in 5% cases. In comparison with international data, our local cohort had a higher rate of follicular thyroid carcinoma. Variation was seen in terms of age, gender distribution, primary tumour size, nodal and distant disease. In Korea, where thyroid cancer screening has been undertaken, smaller tumours, higher rates of nodal disease and lower rates of distant disease are described. Conclusion: In our centre, a higher rate of males is treated with larger primary disease and a higher percentage of follicular carcinoma. The reasons for this geographic variation in clinicopathological features in the UK are unclear. As a result, caution should be applied in translating the international move towards a more conservative approach to DTC in the UK in comparison with other areas of the world.